Decolonial transnational feminisms: some issues about coloniality within feminisms - Caroline Betemps (Revista Estudos Feministas, 2019)
Latin American feminisms embodied since mid-1990 a discussion about their possibilities of action that questioned the fact that many feminist projects designed by western feminists were developed with an underlying notion of ‘universal citizenship’ for the ‘third world women’. Despite the predominance of this hegemonic feminism, other reflections and divergent alignments have appeared in the last years, turning into a rising production of local theoretical knowledge as well as counter-narratives, produced by groups such as the decolonial feminisms, the anti-racist and the anti-capitalist collectives. The turn to the right that Latin America, Europe and US have experienced recently with the increasing conservative governments and their reactionary political imaginaries, requires transnational feminist strategies. The question that brings me here, is how to establish an equitable debate among north-south different feminisms, its dialogues and frictions, without reproducing colonial violence. A dialogue that shares heritages of social struggles, a geopolitical translation understood as practice that does not fall into the repetition of coloniality.